Value of sprinklers to reduce heat stress of lactating sows - David A Nichols; James P Murphy; D S Pollmann; D R Ames (Kansas Agricultural Experiment Station Research Reports, 1982)
Twenty-eight sows and gilts were used to evaluate the value of drip sprinkling to reduce heat stress during lactation. Sprinkled sows had significantly lower respiration rates (P<.05) and consumed significantly more feed during the 21-day lactation. Number of pigs born live, dead, and weaned were not affected by sprinkling. Sprinkled sows tended to wean heavier pigs and lose less weight during lactation but these differences were not significant. These results indicate that a drip cooling for lactating sows is a low cost, effective method to reduce heat stress.; Swine Day, Manhattan, KS, November 11, 1982
Keywords: Swine day; 1982; Kansas Agricultural Experiment Station contribution; no. 82-614-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 422; Swine; Sprinklers; Heat Stress; Lactating Sows